INVESTIGATING THE NEXUS BETWEEN GREEN ENERGY AND ARTIFICIAL INTELLIGENCE (AI) - MITHUN S. ULLAL; ADITYA ANAND; POPESCU VIRGIL; BIRAU RAMONA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
Artificial Intelligence (AI) can enhance the efficient use of green energy and increase the scalability of renewable energy. The global shift towards green energy has to managed and optimized which is a major challenge. Deep learning can play a vital role in predictive maintenance and storage. The data available from renewable energy systems can be analyzed by the artificial intelligence (AI) in real time to predict and manage energy generation and demand response which drastically reduces wastage of energy and distribution of energy can be more efficient. In this context, the integration of AI with renewable energy systems represents a paradigm shift in addressing the global energy crisis. Currently, an increased importance is gained by green technologies in order to obtain a sustainable economic wealth.